PERENCANAAN TATA RUANG BERBASIS RISIKO UNTUK MITIGASI BENCANA INDUSTRI DI KOTA CILEGON - Feranita Tri Wulansari (Jurnal Kebijakan Pembangunan Daerah, 2026)
Industrial disaster risk has not been fully incorporated into the Detailed Spatial Plan (RDTR) of Cilegon City due to constraints in the availability of industrial risk data and information, limited local government capacity, and the relatively recent emergence of industrial disaster management as a policy issue at the regional level. This study seeks to provide evidence-based recommendations to support local governments in strengthening industrial disaster risk reduction strategies, enhancing regional resilience, and promoting safe, resilient, and sustainable industrial development. The research employs a root cause analysis approach, with data collected through focus group discussions, interviews, observations, and document analysis. The study recommends the establishment of a Mayor Regulation on the Prevention and Management of Chemical Emergency Conditions. In addition, industrial disaster risk should be incorporated into the assessment of the Regional Resilience Index (IKD) and supported by the development of government guidelines regarding buffer zones, evacuation routes, and evacuation sites for industrial disaster management. These efforts are expected to strengthen regional resilience and support safe and sustainable industrial development in Cilegon City.